A facile ultrasound assisted high temperature ball milling synthesis of LiFePO4/graphene with enhanced electrochemical performance. (11th October 2018) - Li, Xuetian; Shao, Zhongbao; Liu, Kuiren; Zhao, Qing; Liu, Guangfu; Xu, Binshi
Abstract: LiFePO4 /graphene (LiFePO4 /G) cathode material was prepared by a facile ultrasound assisted high temperature ball milling method. Ultrasound assisted was found to be effective to promote the dispersing of the precursor in solution. Physical and electrochemical properties of LiFePO4 /G were studied. The results exhibited that graphene combined with the LiFePO4 clusters giving rise to a conductive network. LiFePO4 /G displayed a well-crystallized LiFePO4 structure and excellent electrochemical performance. The initial discharge capacities of LiFePO4 /G were 162.8, 156.8, 151.9, 145.8, 137.5 and 121.6 mAhg −1 at rates of 0.1, 0.5, 1.0, 2.0, 5.0 and 10 C, respectively. Moreover, at 0.1 C-rate, the capacity was 160.4 mAhg −1 over 100 cycles with a capacity retention of 98.5%. It is concluded that graphene is a conductive additive which can enhance the electrochemical properties of LiFePO4 . Highlights: LiFePO4 /graphene was obtained by ultrasound assisted high temperature ball milling. Graphene coating on LiFePO4 improved its electronic conductivity. The obtained LiFePO4 /graphene exhibited an excellent electrochemical performance.